Will the impact of the 2009 drought be different from 2002? - Shah, Tushaar; Kishore, Avinash; Hemant, P. (2009)
Groundwater, which has emerged as India's prime adaptive mechanism in times of drought, will play a crucial role this year since the aquifers were recharged in 2006-08. The impact of the drought of 2009 will therefore be less severe than the drought of 2002. Beyond the immediate response, we need to think long term. Instead of pumping money into dams and canals, Indian agriculture will be better off investing in "groundwater banking?. This involves storing surplus flood waters in aquifers which can be drawn upon in times of need.